Effectiveness of Problem-Based Learning Method in Online Learning - Yuantari, Maria Goretti Catur; Isworo, Slamet; Sugianto, Zaenal (Edusight International Journal of Multidisciplinary Studies, 2025)
The COVID-19 pandemic that occurred in early 2020 had an impact on the learning system in universities that switched to an online learning system. This causes the learning process to experience various challenges, especially in the health sector which requires direct practice. The purpose of this study was to assess the effectiveness of the Problem-Based Learning (PBL) method for students of the Faculty of Health, Dian Nuswantoro University in online learning. The method used was quantitative analytic with a cross-sectional approach, the respondents in this study were 326 students from three study programs. The results showed that 58% of students with good learning achievement, 52% had high learning interest, and 79% obtained good learning outcomes. 59% of learning briefings from lecturers were good, and 51% of the field learning process was good. Problem-based learning (PBL) is proven to improve students' understanding of course material, encourage active participation, and help develop problem-solving and critical-thinking skills. However, it is problematic if there is a lack of direct interaction with lecturers and limited internet access. To improve the effectiveness of PBL in the future, it is necessary to improve technological infrastructure, intensive training for lecturers, and the development of more interactive digital learning platforms